Social Behavior in Buddhist Communities in Central Java - Suyatno, Tri; Asih, Situ; Novianti, Novianti; Mugiyo, Mugiyo (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2024)
The purpose of this study is to analyze the social behavior of Buddhist communities in Central Java. That in Buddhists in Central Java have Communication Patterns and Poa social behavior in society. The sample of this study is Pati Regency and Jepara Regency where these two districts are one of the bases of Buddhism in Central Java. The method in this study is a descriptive qualitative approach method. Where this research multiplies and collects information from sources with documentation methods, archival records, interviews, direct observation, participatory observation, and physical artifacts. The result of this study is the formation of Groupthink in the Buddhist community in Central Java Province, inseparable from the participation of leaders or administrators in Buddhist community groups. Buddhist community groups grow high cohesiveness, as for some evidence that states that Buddhist community groups have high cohesiveness, among others; (1) the existence of a relationship or relationship between individuals with one another is very close. (2) Sense of belonging or sense of belonging to the Group, (3) High loyalty to the Group, and (4) Solidarity among group members is very strong